Negative electrode for lithium secondary battery and lithium secondary battery including the same

A lithium secondary battery with a silicon concentration gradient in the negative electrode active material layer addresses performance limitations, improving cycle life and high-temperature storage by managing volume expansion and resistance.

JP7621205B2Active Publication Date: 2025-01-24SAMSUNG SDI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2021106546
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-26
Filing Date
2021-06-28
Publication Date
2025-01-24
Estimated Expiration
2041-06-28

AI Technical Summary

Technical Problem

Existing lithium secondary batteries face challenges in achieving excellent cycle life characteristics and high-temperature storage performance due to the limitations of current negative electrode materials, particularly when using silicon-based substances.

Method used

A lithium secondary battery design featuring a negative electrode with a structured active material layer that includes a concentration gradient of silicon content, varying from a higher concentration near the current collector to a lower concentration further away, combined with carbon-based substances, to enhance performance.

Benefits of technology

The structured silicon distribution improves cycle life characteristics and high-temperature storage performance by managing volume expansion during charging and discharging, leading to enhanced battery capacity and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621205000003
    Figure 0007621205000003
  • Figure 0007621205000004
    Figure 0007621205000004
  • Figure 0007621205000005
    Figure 0007621205000005
Patent Text Reader

Abstract

To provide a negative electrode for a lithium secondary battery exhibiting excellent battery performance and cycle life characteristics, and a lithium secondary battery including the negative electrode.SOLUTION: In a negative electrode for a lithium secondary battery and a lithium secondary battery including the same, the negative electrode includes a current collector and a negative electrode active material layer located on the current collector, and the negative electrode active material layer includes a first region adjacent to the current collector and a second region that is not in contact with the current collector. The negative electrode active material layer includes a carbon substance and a Si-based material containing Si, and the content of Si contained in the negative electrode active material layer differs between the first region and the second region.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same. [Background technology]

[0002] Recently, with the rapid spread of electronic devices that use batteries, such as mobile phones, laptops, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have relatively high capacity is rapidly increasing. In particular, lithium secondary batteries are attracting attention as a driving power source for portable devices because of their light weight and high energy density. As a result, research and development to improve the performance of lithium secondary batteries is being actively conducted.

[0003] A lithium secondary battery is a battery that contains positive and negative electrodes, which include active materials capable of intercalating and deintercalating lithium ions, and an electrolyte. It produces electrical energy through oxidation and reduction reactions that occur when lithium ions are intercalated and deintercalated at the positive and negative electrodes.

[0004] The positive electrode active material of the lithium secondary battery is mainly a transition metal compound such as lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, etc. The negative electrode active material is mainly a crystalline carbon material such as natural graphite or artificial graphite, or an amorphous carbon material. Summary of the Invention [Problem to be solved by the invention]

[0005] One embodiment provides a negative electrode for a lithium secondary battery that exhibits excellent battery performance and cycle life characteristics. Another embodiment provides a lithium secondary battery including the negative electrode. [Means for solving the problem]

[0006] One embodiment provides a negative electrode for a lithium secondary battery, comprising: a current collector; and a negative electrode active material layer located on the current collector, the negative electrode active material layer comprising a first region adjacent to the current collector and a second region not in contact with the current collector, the negative electrode active material layer comprising a carbon material and a Si-based material including Si, and a content of Si in the negative electrode active material layer differs between the first region and the second region.

[0007] The Si content may have a concentration gradient that increases from the second region toward the first region.

[0008] In one embodiment, the content of Si present in the first region may be 2 to 25 times the content of Si present in the second region.

[0009] The carbon material may be crystalline carbon, which may be synthetic graphite, natural graphite, or a combination thereof.

[0010] The Si-based material may include a composite material including Si particles and a first carbon-based material.

[0011] In one embodiment, the Si-based material may include a core in which Si particles and a second carbon-based material are mixed, and a third carbon-based material surrounding the core.

[0012] The thickness of the first region may be 1% to a maximum of 75% of the total thickness of the negative electrode active material layer.

[0013] According to another embodiment, there is provided a lithium secondary battery comprising the negative electrode, a positive electrode, and an electrolyte. Effect of the Invention

[0014] The negative electrode active material according to an embodiment may exhibit excellent cycle life characteristics and excellent high-temperature storage characteristics. [Brief description of the drawings]

[0015] [Figure 1] 1 is a diagram illustrating a structure of a negative electrode for a lithium secondary battery according to an embodiment; [Diagram 2] 1 is a schematic diagram of a lithium secondary battery according to an embodiment; [Diagram 3] 1 is a graph showing room temperature cycle life characteristics of half cells produced in Examples 1 and 2 and Comparative Example 1. [Figure 4] 1 is a graph showing high-temperature cycle life characteristics of half cells produced in Examples 1 and 2 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, preferred embodiments of the present invention will be described in detail, but they are given by way of example only and are not intended to limit the present invention, which is defined by the scope of the following claims.

[0017] According to one embodiment, a negative electrode for a lithium secondary battery includes a current collector and a negative electrode active material layer disposed on the current collector, the negative electrode active material layer including a first region adjacent to the current collector and a second region not adjacent to the current collector. The negative electrode active material layer includes a carbon material and a Si-based material including Si, and the Si content of the negative electrode active material layer is different between the first region and the second region.

[0018] Referring to FIG. 1, according to one embodiment, a negative electrode 1 includes a current collector 3 and a negative electrode active material layer 5, and includes a first region 5a adjacent to the current collector 3 and a second region 5b not adjacent to the current collector 3.

[0019] The first region may represent a region corresponding to 1% to 75% of the total thickness of the negative electrode active material layer. According to one embodiment, the first region may represent a region corresponding to 1% to 50% of the total thickness of the negative electrode active material layer. That is, when the total thickness of the negative electrode active material layer is taken as 100%, the first region may be a region corresponding to a minimum of 1% thickness, or a region corresponding to a maximum of 75% thickness, and according to one embodiment, a region corresponding to a maximum of 50% thickness.

[0020] This means that the thickness of the first region may be 1% or more and 75% or less when the total thickness of the negative electrode active material layer is taken as 100%. In Fig. 1, "a" is the thickness of the first region, and the thickness of "a" may be at least 1% and at most 75% of the total thickness (h) of the negative electrode active material, and in one embodiment, at most 50%. 1 is the thickness of the second region, and the thickness of b may be at least 25% and at most 99% of the total thickness (h) of the negative electrode active material, and in one embodiment, may be at most 50%. In one embodiment, the second region is formed in direct contact with the first region, and the first region is formed in direct contact with the current collector.

[0021] The Si content in the negative electrode active material layer is different between the first region and the second region, for example, the Si content in the first region is different from the Si content in the second region. According to one embodiment, Si exists in a concentration gradient that increases from the second region toward the first region, and the Si content in the first region may be 2 to 25 times the Si content in the second region. That is, the Si content in the first region may be 2 to 25 times higher than the Si content in the second region. According to another embodiment, the Si content in the negative electrode active material layer may increase by 5 wt % to 8 wt % for each region corresponding to 25% of the thickness from the outermost surface of the second region toward the first region, when the total thickness of the negative electrode active material layer is taken as 100%.

[0022] When the Si content is increased under the above conditions, the expansion of the active material layer during charging and discharging can be more effectively suppressed, and the cycle life characteristics can be improved.

[0023] In this manner, the first and second regions of the negative electrode active material layer, for example the lower and upper regions, have different Si contents, and in particular the Si content in the second region is lower than the Si content in the first region. According to one embodiment, the Si content has a concentration gradient increasing from the second region to the first region, thereby reducing resistance and improving high-rate charge / discharge characteristics and cycle life characteristics.

[0024] Such an effect can be more pronounced when the content of Si contained in the first region is 2 to 25 times the content of Si contained in the second region.

[0025] Even if the Si content of the first region and the second region is different, if the Si content of the second region is higher than that of the first region, it is not appropriate because the effect of improving the high rate charge / discharge characteristics and cycle life characteristics cannot be obtained due to the increase in resistance and initial deterioration caused by the high Si content in the second region.

[0026] The negative electrode active material layer may have a silicon content of 1 to 25 wt % based on the total weight of the negative electrode active material layer. When the silicon content is within this range, a capacity improvement effect per battery volume can be obtained.

[0027] The carbon material may be crystalline carbon, which may be synthetic graphite, natural graphite, or a combination thereof.

[0028] The weight ratio of the carbonaceous material and the Si-based material in the negative electrode active material layer may be 0.1:100 to 2000:100. When the weight ratio of the carbonaceous material and the Si-based material in the negative electrode active material layer is within the above range, the volume suppression effect of silicon is excellent and the conductivity characteristics are excellent, which is appropriate.

[0029] In one embodiment, the Si-based material may include a composite including Si particles and a first carbon-based material. The first carbon-based material may be amorphous carbon or crystalline carbon. A specific example of the composite may include a core in which Si particles and a second carbon-based material are mixed, and a third carbon-based material surrounding the core. The second carbon-based material and the third carbon-based material may be the same or different from each other, and may be amorphous carbon or crystalline carbon.

[0030] The amorphous carbon may be pitch carbon, soft carbon, hard carbon, mesophase pitch carbon, calcined coke, carbon fiber, or a combination thereof, and the crystalline carbon may be artificial graphite, natural graphite, or a combination thereof.

[0031] The particle size of the Si particles may be 10 nm to 30 μm, and in one embodiment, 10 nm to 1000 nm, and in another embodiment, 20 nm to 150 nm. When the average particle size of the Si particles is within the above range, volume expansion that occurs during charging and discharging can be suppressed, and the conductive path can be prevented from being broken due to particle crushing during charging and discharging.

[0032] In the present specification, the particle size may be the average particle size of the particle. In this case, the average particle size may refer to the particle size D50 measured by the cumulative volume. Unless otherwise defined in the present specification, the particle size D50 refers to the average particle size D50, which means the diameter of particles whose cumulative volume is 50% by volume in the particle size distribution.

[0033] The average particle size D50 can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer, a transmission electron microscope photograph, or a scanning electron microscope photograph. As another method, it can be measured using a measuring device using dynamic light-scattering, and the number of particles for each particle size range can be counted by performing data analysis, and the average particle size D50 value can be calculated from this.

[0034] When the Si-based material includes Si particles and a first carbon-based material, the content of the Si particles may be 30% by weight to 70% by weight, and according to one embodiment, 40% by weight to 50% by weight. The content of the first carbon-based material may be 70% by weight to 30% by weight, and according to one embodiment, 50% by weight to 60% by weight. When the content of the Si particles and the first carbon-based material is within the above range, high capacity characteristics can be exhibited.

[0035] When the Si-based material is a core in which Si particles and a second carbon-based material are mixed, and a third carbon-based material surrounding the core, the third carbon-based material may be present in a thickness of 5 nm to 100 nm. The third carbon-based material may be 1 wt% to 50 wt% of the total Si-based material (100 wt%), the Si particles may be 30 wt% to 70 wt% of the total Si-based material (100 wt%), and the second carbon-based material may be 20 wt% to 69 wt% of the total Si-based material (100 wt%). When the contents of the Si particles, the third carbon-based material, and the second carbon-based material are within the above ranges, the discharge capacity is excellent and the capacity retention rate can be improved, which is appropriate.

[0036] The negative active material layer may include the negative active material and a binder, and may optionally further include a conductive material.

[0037] The content of the negative active material may be 95 wt % to 99 wt % based on the total weight of the negative active material layer.

[0038] The content of the binder may be 1 wt% to 5 wt% based on the total weight of the negative active material layer. When a conductive material is further included, the negative active material may be 90 wt% to 98 wt%, the binder may be 1 wt% to 5 wt%, and the conductive material may be 1 wt% to 5 wt%.

[0039] The binder serves to adhere the negative active material particles to each other and to the current collector. The binder may be a non-aqueous binder, an aqueous binder, or a combination thereof.

[0040] Examples of the non-aqueous binder include ethylene propylene copolymers, polyacrylonitrile, polystyrene, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0041] The aqueous binder may be styrene-butadiene rubber (SBR), acrylated styrene-butadiene rubber (ABR), acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, a polymer containing ethylene oxide, polyvinylpyrrolidone, polypropylene, polyepichlorohydrin, polyphosphazene, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or a combination thereof.

[0042] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included as a thickener. The cellulose-based compound may be a mixture of one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof. The alkali metal may be Na, K, or Li. The amount of the thickener used may be 0.1 to 3 parts by weight based on 100 parts by weight of the negative electrode active material.

[0043] The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause chemical changes in the battery that is constructed and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers of copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials including mixtures thereof.

[0044] The current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0045] Hereinafter, the negative electrode according to one embodiment can be manufactured by the following steps. Two or more, for example, two or more to four or less, negative electrode active material layer compositions having different Si contents may be prepared. The two or more negative electrode active material compositions have the same composition except for the Si content, and the negative electrode active material layer compositions include a negative electrode active material, a binder, and optionally a conductive material, and also include a solvent. In this case, the negative electrode active material includes a carbon material and a Si-based material containing Si, and the mixing ratio of the carbon material to the Si-based material may be 0.1:100 to 2000:100 by weight.

[0046] When two negative electrode active material layer compositions are prepared, the first negative electrode active material layer composition may have a Si content of 10 wt % to 25 wt % based on 100 wt % of the total solid content of the first negative electrode active material layer composition, and the second negative electrode active material layer composition may have a Si content of 1 wt % to 15 wt % based on 100 wt % of the total solid content of the second negative electrode active material layer composition.

[0047] In addition, when three or more negative electrode active material layer compositions are prepared, the negative electrode active material layer compositions may be prepared so that the Si content increases by 5 wt% to 8 wt% in increments within a range of a minimum of 1 wt% to a maximum of 25 wt% based on 100 wt% of the total solid content of the negative electrode active material layer composition.

[0048] Negative electrode active material layer compositions having different Si contents are simultaneously applied to the current collector, for example, a first negative electrode active material layer composition and a second negative electrode active material layer composition are simultaneously applied, and at this time, the first negative electrode active material layer composition can be directly applied to the current collector. That is, the negative electrode active material layer composition having a higher Si content can be directly applied to the current collector. Then, drying and rolling are performed to form a negative electrode active material layer.

[0049] In this way, by simultaneously applying the negative electrode active material layer compositions having different Si contents, a negative electrode active material layer having different Si contents in the first and second regions of the negative electrode active material layer can be formed. In addition, the negative electrode active material layer may have a concentration gradient of Si content. When two negative electrode active material compositions having different Si contents are used, the conditions of the drying process can be appropriately adjusted to form a negative electrode active material layer having a concentration gradient of Si content. In addition, in the application process, the thickness of the first and second regions can be adjusted by adjusting the solid content of the active material layer composition and the hydraulic pressure of the machine used.

[0050] The rolling step can be carried out under conditions generally used in the art. Another embodiment provides a lithium secondary battery comprising the negative electrode, a positive electrode, and an electrolyte. The positive electrode includes a current collector and a positive electrode active material layer formed on the current collector.

[0051] As the positive electrode active material, a compound capable of reversible intercalation and deintercalation of lithium (lithiated intercalation compound) can be used. Specifically, one or more of composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof can be used. More specifically, a compound represented by any one of the following chemical formulas can be used. Li a A 1-b X b D2(0.90≦a≦1.8, 0≦b≦0.5);Li a A 1-b X b O 2-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05);Li a E 1-b X b O 2-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05);Li a E 2-b X b O 4-c D c (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05);Li a Ni 1-b-c Co b X c D α (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.5, 0<α≦2);Li a Ni 1-b-c Co b X c O 2-α T α (0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.5, 0<α<2);Li a Ni 1-b-c Co b X c O 2-α T2(0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.5, 0<α<2);Lia Ni 1-b-c Mr b X c D α (0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.5、0<α≦2);Li a Ni 1-b-c Mr b X c O 2-α T α (0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.5、0<α<2);Li a Ni 1-b-c Mr b X c O 2-α T2(0.90≦a≦1.8、0≦b≦0.5、0≦c≦0.5、0<α<2);Li a Ni b HAVE BEEN c G d O2(0.90≦a≦1.8、0≦b≦0.9、0≦c≦0.5、0.001≦d≦0.1);Li a Ni b Co c Mr d G e O2(0.90≦a≦1.8、0≦b≦0.9、0≦c≦0.5、0≦d≦0.5、0≦e≦0.1);Li a Ni b Co c Al d G e O2(0.90≦a≦1.8、0≦b≦0.9、0≦c≦0.5、0≦d≦0.5、0≦e≦0.1);Li a Ni b Co c Mr d G e O2(0.90≦a≦1.8、0≦b≦0.9、0≦c≦0.5、0≦d≦0.5、0.001≦e≦0.1);Li a NiG b O2(0.90≦a≦1.8、0.001≦b≦0.1);Li a CoG b O2(0.90≦a≦1.8、0.001≦b≦0.1);Li a Mr 1-b G b O2(0.90≦a≦1.8、0.001≦b≦0.1);Lia Mn2G b O4(0.90≦a≦1.8, 0.001≦b≦0.1);Li a Mn 1-g G g PO4(0.90≦a≦1.8, 0≦g≦0.5);QO2;QS2;LiQS2;V2O5;LiV2O5;LiZO2;LiNiVO4;Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) Fe2(PO4)3(0≦f≦2);Li a FePO4(0.90≦a≦1.8)

[0052] In the above formula, A is selected from the group consisting of Ni, Co, Mn, and combinations thereof; X is selected from the group consisting of Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements, and combinations thereof; D is selected from the group consisting of O, F, S, P, and combinations thereof; E is selected from the group consisting of Co, Mn, and combinations thereof; T is selected from the group consisting of F, S, P, and combinations thereof; G is selected from the group consisting of Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, and combinations thereof; Q is selected from the group consisting of Ti, Mo, Mn, and combinations thereof; Z is selected from the group consisting of Cr, V, Fe, Sc, Y, and combinations thereof; and J is selected from the group consisting of V, Cr, Mn, Co, Ni, Cu, and combinations thereof.

[0053] Of course, the compound may have a coating layer on its surface, or the compound may be mixed with a compound having a coating layer. The coating layer may include at least one coating element compound selected from the group consisting of oxides of coating elements, hydroxides of coating elements, oxyhydroxides of coating elements, oxycarbonates of coating elements, and hydroxycarbonates of coating elements. The compounds forming the coating layer may be amorphous or crystalline. The coating elements included in the coating layer may be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating layer forming process may use any coating method as long as the compound can be coated with such elements in a manner that does not adversely affect the physical properties of the positive electrode active material (e.g., spray coating, immersion method, etc.), and this is well understood by those skilled in the art, so a detailed description will be omitted.

[0054] In the positive electrode, the content of the positive electrode active material may be 90 wt % to 98 wt % based on the total weight of the positive electrode active material layer.

[0055] In an embodiment, the positive electrode active material layer may further include a binder and a conductive material, each of which may be in an amount of 1 wt % to 5 wt % based on the total weight of the positive electrode active material layer.

[0056] The binder serves to adhere the positive electrode active material particles to each other and to adhere the positive electrode active material to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0057] The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause chemical changes in the battery that is constructed and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers of copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials containing mixtures thereof.

[0058] The current collector may be made of Al, but is not limited thereto.

[0059] The electrolyte includes a non-aqueous organic solvent and a lithium salt. The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move.

[0060] The non-aqueous organic solvent may be a carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvent.

[0061] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, and caprolactone. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. In addition, examples of the alcohol solvent that can be used include ethyl alcohol and isopropyl alcohol, and examples of the aprotic solvent that can be used include nitriles such as R-CN (R is a hydrocarbon group having a linear, branched, or cyclic structure with 2 to 20 carbon atoms and may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes.

[0062] The organic solvent may be used alone or in combination of two or more thereof. When the organic solvent is used in combination of two or more thereof, the mixing ratio may be appropriately adjusted depending on the desired battery performance, which is widely understood by those skilled in the art.

[0063] In addition, in the case of the carbonate-based solvent, it is preferable to use a mixture of cyclic carbonate and chain carbonate in a volume ratio of 1:1 to 1:9, which is shown to provide excellent electrolyte performance.

[0064] The organic solvent may further include an aromatic hydrocarbon-based organic solvent in addition to the carbonate-based solvent, and the carbonate-based solvent and the aromatic hydrocarbon-based organic solvent may be mixed in a volume ratio of 1:1 to 30:1.

[0065] As the aromatic hydrocarbon organic solvent, an aromatic hydrocarbon compound represented by the following formula 1 can be used.

[0066] [ka]

[0067] (In the above chemical formula 1, R1 to R6 are the same or different and are selected from the group consisting of hydrogen, halogen, an alkyl group having 1 to 10 carbon atoms, a haloalkyl group, and combinations thereof.)

[0068] Specific examples of the aromatic hydrocarbon organic solvent include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, It is selected from the group consisting of fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, and combinations thereof.

[0069] The electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound represented by the following Formula 2 as a life-improving additive in order to improve the battery life.

[0070] [ka]

[0071] (In the above formula 2, R7 and R8 are the same or different and are selected from the group consisting of hydrogen, a halogen group, a cyano group (CN), a nitro group (NO2), and a fluorinated alkyl group having 1 to 5 carbon atoms, and at least one of R7 and R8 is selected from the group consisting of a halogen group, a cyano group (CN), a nitro group (NO2), and a fluorinated alkyl group having 1 to 5 carbon atoms, provided that R7 and R8 are not all hydrogen.)

[0072] Representative examples of the ethylene carbonate-based compound include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, etc. When such a life-improving additive is further used, the amount of the additive used can be appropriately adjusted.

[0073] The lithium salt is dissolved in an organic solvent and acts as a lithium ion source in the battery to enable basic lithium secondary battery operation and promote the movement of lithium ions between the positive and negative electrodes. Representative examples of such lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide: LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 The electrolyte contains one or more supporting electrolyte salts selected from the group consisting of LiCl, LiI, and LiB(C2O4)2 (lithium bis(oxalato)borate: LiBOB) (where x and y are natural numbers, for example, integers of 1 to 20). The lithium salt is preferably used at a concentration within a range of 0.1M to 2.0M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can be effectively transferred.

[0074] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multi-layer film of two or more layers of these may be used, and of course, a mixed multi-layer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator may be used.

[0075] An exploded perspective view of a lithium secondary battery according to an embodiment of the present invention is shown in Fig. 2. Although the lithium secondary battery according to the embodiment is described as a square type, the present invention is not limited thereto and may be applied to batteries of various shapes such as a cylindrical type and a pouch type.

[0076] 2, a lithium secondary battery 100 according to an embodiment may include an electrode assembly 40 in which a separator 30 is interposed between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).

[0077] Examples and comparative examples of the present invention will be described below. However, the following examples are merely examples of the present invention, and the present invention is not limited to the following examples. EXAMPLES

[0078] Example 1 A first negative electrode active material slurry was prepared by mixing 87.5 wt% artificial graphite, 10 wt% Si-based material, 1.0 wt% carboxymethyl cellulose, and 1.5 wt% styrene-butadiene rubber in pure water. In this case, a Si-carbon composite was used as the Si-based material, which was a core containing artificial graphite and silicon particles, and the surface of the core was coated with soft carbon. The thickness of the soft carbon coating layer was 20 nm, and the average particle size D50 of the silicon particles was 100 nm.

[0079] A second negative electrode active material slurry was prepared by mixing 92.5 wt% artificial graphite, 5 wt% Si-based material, 1.0 wt% carboxymethyl cellulose, and 1.5 wt% styrene-butadiene rubber in pure water. In this case, a Si-carbon composite was used as the Si-based material, which was a core containing artificial graphite and silicon particles, and the surface of the core was coated with soft carbon. The thickness of the soft carbon coating layer was 20 nm, and the average particle size D50 of the silicon particles was 100 nm.

[0080] The first and second negative active material layer slurries were simultaneously applied to a copper foil current collector, and then dried and rolled to form a negative active material layer, finally manufacturing a negative electrode. In the negative active material layer, a region adjacent to the current collector, which corresponds to 50% of the total thickness of the negative active material layer, was classified as a first region, and a region not in contact with the current collector, which corresponds to the remaining 50%, was classified as a second region. In the manufactured negative active material layer, the Si content in the first region was formed to be twice as high as the Si content in the second region. In addition, the Si content in the entire negative active material layer was 7.5 wt% with respect to the total weight of the negative active material layer.

[0081] A half-cell was fabricated in a conventional manner using the negative electrode, the lithium metal counter electrode, and an electrolyte, which was a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate (volume ratio: 30:50:20) in which 1.5 M LiPF6 was dissolved as an electrolyte.

[0082] Example 2 A first negative electrode active material slurry was prepared by mixing 83.5 wt% artificial graphite, 14 wt% Si-based material, 1.0 wt% carboxymethyl cellulose, and 1.5 wt% styrene-butadiene rubber in pure water. In this case, a Si-carbon composite was used as the Si-based material, which was a core containing artificial graphite and silicon particles, and the surface of the core was coated with soft carbon. The thickness of the soft carbon coating layer was 20 nm, and the average particle size D50 of the silicon particles was 100 nm.

[0083] A second negative electrode active material slurry was prepared by mixing 96.5 wt% artificial graphite, 1 wt% Si-based material, 1.0 wt% carboxymethyl cellulose, and 1.5 wt% styrene-butadiene rubber in pure water. In this case, a Si-carbon composite was used as the Si-based material, which was a core containing artificial graphite and silicon particles, and the surface of the core was coated with soft carbon. The thickness of the soft carbon coating layer was 20 nm, and the average particle size D50 of the silicon particles was 100 nm.

[0084] The first and second negative electrode active material slurries were simultaneously applied to a copper foil current collector, and then dried and rolled. At this time, the drying process was controlled under conditions sufficient to obtain a concentration gradient in which the Si content in the second region increased in a direction toward the first region, thereby forming a negative electrode active material layer having a concentration gradient.

[0085] In this case, the concentration gradient was such that the Si content increased by 6 wt % for each region corresponding to a thickness of 25% from the outermost surface of the second region toward the first region, and the average Si content in the first region was 5 times higher than the average Si content in the second region. A half cell was fabricated in the same manner as in Example 1, except that the negative electrode was used.

[0086] Comparative Example 1 A first negative electrode active material slurry was prepared by mixing 82.5 wt% artificial graphite, 15 wt% Si-based material, 1.0 wt% carboxymethyl cellulose, and 1.5 wt% styrene-butadiene rubber in pure water. In this case, a Si-carbon composite was used as the Si-based material, which was a core containing artificial graphite and silicon particles, and the surface of the core was coated with soft carbon. The thickness of the soft carbon coating layer was 20 nm, and the average particle size D50 of the silicon particles was 100 nm.

[0087] A second negative electrode active material slurry was prepared by mixing 82.5 wt% artificial graphite, 15 wt% Si-based material, 1.0 wt% carboxymethyl cellulose, and 1.5 wt% styrene-butadiene rubber in pure water. In this case, a Si-carbon composite was used as the Si-based material, which was a core containing artificial graphite and silicon particles, and the surface of the core was coated with soft carbon. The thickness of the soft carbon coating layer was 20 nm, and the average particle size D50 of the silicon particles was 100 nm.

[0088] The first and second negative active material slurries were applied to a copper foil current collector, and then dried and rolled to form a negative active material layer, finally manufacturing a negative electrode. In the negative active material layer, a region adjacent to the current collector, which corresponds to 50% of the total thickness of the negative active material layer, was classified as a first region, and a region not in contact with the current collector, which corresponds to the remaining 50%, was classified as a second region. In the manufactured negative active material layer, the Si content in the first region was the same as the Si content in the second region. A half cell was fabricated in the same manner as in Example 1, except that the negative electrode was used.

[0089] Experimental example 1) Room temperature cycle life characteristic evaluation The half-cells prepared according to Examples 1 and 2 and Comparative Example 1 were charged and discharged 200 times at room temperature (25° C.) at 0.5 C and 0.5 C. The ratio (%) of the 200th discharge capacity to the initial discharge capacity was calculated, and the results are shown in FIG.

[0090] As shown in FIG. 3, when the negative electrode active material layer has a first region in contact with the current collector and a second region not in contact with the current collector, and the Si content in the first region is two or five times higher than the Si content in the second region, the room temperature cycle life characteristics are excellent.

[0091] Experimental example 2) High temperature cycle life characteristic evaluation The half cells prepared according to Examples 1 and 2 and Comparative Example 1 were charged and discharged 200 times at a high temperature (45° C.) at 0.5 C and 0.5 C. The ratio (%) of the 200th discharge capacity to the initial discharge capacity was calculated, and the results are shown in FIG.

[0092] As shown in FIG. 4, when the negative electrode active material layer has a first region in contact with the current collector and a second region not in contact with the current collector, and the Si content in the first region is two or five times higher than the Si content in the second region, the high-temperature cycle life characteristics are excellent.

[0093] Although a preferred embodiment of the present invention has been described above, the present invention is not limited thereto, and can be embodied in various modified forms within the scope of the claims, the detailed description of the invention, and the accompanying drawings, which of course also fall within the scope of the present invention. [Explanation of symbols]

[0094] 1 negative electrode 3 Current collector 5 Negative electrode active material layer 5a 1st area 5b 2nd area 10 positive electrode 20 negative electrode 30 Separator 40 Electrode assembly 50 cases 100 Lithium secondary battery

Claims

1. A current collector; and a negative electrode active material layer disposed on the current collector, the negative electrode active material layer includes a first region adjacent to the current collector and a second region not in contact with the current collector, the negative electrode active material layer includes a Si-based material and a carbon material, and a Si content in the negative electrode active material layer is different between the first region and the second region, The Si-based material is a composite material including a core in which Si particles and a second carbon-based material are mixed, and a third carbon-based material coated on the surface of the core, the second carbon-based material is crystalline carbon, and the third carbon-based material is amorphous carbon; the carbon material is crystalline carbon; The content of Si contained in the first region is 2 to 5 times the content of Si contained in the second region.

2. 2 . The negative electrode for a lithium secondary battery according to claim 1 , wherein the Si exists in a concentration gradient that increases from the second region toward the first region.

3. 3. The negative electrode for a lithium secondary battery according to claim 1, wherein the crystalline carbon is artificial graphite, natural graphite, or a combination thereof.

4. 4 . The negative electrode for a lithium secondary battery according to claim 1 , wherein a thickness of the first region is in a range of 1% to 75% of a total thickness of the negative electrode active material layer.

5. An anode according to any one of claims 1 to 4; a positive electrode; and A lithium secondary battery comprising an electrolyte.

Citation Information

Patent Citations

  • Silicon-containing negative plate and preparation method thereof and lithium ion battery

    CN110993891A